EVALUASI PELAKSANAAN LAYANAN INFORMASI DENGAN MEDIA BK DI MTsN 2 MEDAN - Amal Hayati; Adeliya Ramadhani; Siti R Nur Uli Isnaini (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The purpose of this study is to reveal the results of the evaluation of the implementation of information services using various media of Guidance and Counseling at MTsN 2 Medan. Information services are one of the types of services in guidance and counseling. The use of media in the implementation of information services aims to help guidance and counseling teachers get students' attention and facilitate the delivery of service materials clearly, accurately, and comprehensively. This research was conducted using a quantitative method with a descriptive statistical analysis process to obtain the average score, maximum value, and minimum value, which indicate the evaluation results of information services using media of guidance and counseling. The findings of this study reveal that the implementation of information services with media of guidance and counseling at MTsN 2 Medan is quite good, with 11 respondents believing that the information services using media of guidance and counseling were well implemented and 20 respondents believing that the information services using media of guidance and counseling were implemented fairly well. With evaluation results showing a positive direction, guidance and counseling teachers can further enhance guidance and counseling services by visiting classrooms weekly to meet students' specific information needs. The implementation of information services with media of guidance and counseling that is appropriate for the student's circumstances such as personal, social, learning and career, as well as the use of varied BK media and clear materials is very helpful for students.